Prevalence of childhood hypertension and pre-hypertension in school going children of Bangalore rural district: a cross sectional study - Sabapathy, Sarala; B. A., Nagaraju; C. N., Bhanuprakash (International Journal of Contemporary Pediatrics, 2017)
Background: Childhood hypertension is one of the rising public health problems. Childhood hypertension may lead to significant morbidity and mortality. The objective of the study was to find the prevalence of childhood hypertension and pre-hypertension in school going children of Bangalore Rural District. Methods: A cross sectional study conducted between July 2015 to January 2016 in Bangalore Rural District. Total of 1024 school children aged between 6 to 16 years were examined. Both private and government school children were examined during the study. Anthropometric measurements like Weight, Height, BMI and Blood Pressure were measured for each child. Then children were categorized as hypertensive or pre-hypertensive based on Fourth Task force report and into obese or overweight based on WHO BMI charts. Results: Prevalence of hypertension was 2.7% and pre-hypertension is 3.2%. In government school children 1.7% were hypertensive and 0.8% were pre-hypertensive. In private school children 3.5% were hypertensive and 5.1% were pre-hypertensive. Among children with hypertension 39% children were obese and 50% were overweight. Conclusions: Childhood hypertension is prevalent in both government and private schools, with high prevalence in private schools. Blood pressure measurement should be made mandatory in all school children.